EU som normentreprenör för ekologisk hållbarhet? En kvalitativ innehållsanalys av handelsavtalet mellan EU och Kenya - Hreljic,Amar; Erlandsson,Wilma (2025)
This study delves into how the European Union acts as a norm entrepreneur, promoting ecological sustainability through external trade policy. By applying qualitative content analysis on the Paris Agreement, the Convention on Biological Diversity and the recent Economic Partnership Agreement between the EU and Kenya, the research identifies environmental norms ingrained in these agreements and evaluates their legal robustness. Drawing on the theories of sociological institutionalism and Normative Power Europe, as well as the framework of legalization, the analysis assesses the degree of obligation, precision and delegation associated with key norms. Findings indicate that the EPA primarily strengthens market-oriented and technocratic sustainability norms, emphasizing the adaptability of economic systems to environmental goals, while sidelining norms rooted in intrinsic environmental values or traditional knowledge due to their incompatibility with western values. Additionally, the analysis concludes that transparency, evaluations and public reports are encouraged in order to circumvent state sovereignty which can otherwise impede the transition towards ecological sustainability. The study thereby adds to the literature on EU external governance and norm transfer, by highlighting the significance of norms and the need for contextual awareness. Ultimately, it raises critical questions about the suitability and effectiveness of EU norms in external settings.
Keywords: Normentreprenörskap; normer; sociologisk institutionalism; Normative Power Europe; klimat; biologisk mångfald; hållbar utveckling; handel; kvalitativ innehållsanalys; EU; Kenya; Parisavtalet; convention on biological diversity